Aluminum Hydrides Stabilized by N‐Heterocyclic Imines as Catalysts for Hydroborations with Pinacolborane. Issue 22 (3rd November 2016) - Franz, Daniel; Sirtl, Lorenz; Pöthig, Alexander; Inoue, Shigeyoshi
Abstract : The catalytic activity of the NHI‐substituted aluminum hydrides L Mes NAlH2 2 (1a ), L Dip NAlH2 2 (1b ), L Mes NAl(H)OTf2 (2a ), and L Dip NAl(H)OTf2 (2b ) in the hydroboration of terminal alkynes (for1 ), as well as carbonyl compounds (for2 ) with pinacolborane (4, 4, 5, 5‐tetramethyl‐1, 3, 2‐dioxaborolane) is investigated (L Mes N = 1, 3‐dimesityl‐imidazolin‐2‐imino, Mes = 2, 4, 6‐trimethylphenyl, L Dip N = 1, 3‐bis(2, 6‐diisopropylphenyl)‐imidazolin‐2‐imino, Tf = triflyl). With the implementation of1 as a catalyst, the hydroboration of selected terminal arylalkynes requires elevated temperature (80 °C) to proceed. The less sterically congested1a produces faster conversions than the bulkier1b . With the use of2 as a catalyst, the hydroboration of carbonyl compounds occurs at room temperature. An increased steric hindrance of the catalyst (2a vs.2b ) does not mitigate the rate of conversion to a relevant degree. Abstract :